Information System of Achievement Scholarship Recipients (Case Study: SDN I Glp Minyeuk Sigli) - Qushary, Muhammad Al; Salam, Abdus (International Journal Education and Computer Studies (IJECS), 2021)
Achievement scholarship is one of the SDN I Glp Minyeuk Sigli programs which is managed by a school that has the aim of helping children who excel but are less well off financially in school, it is hoped that with this achievement scholarship program many children cannot afford the cost but have academic achievement can continue school without having to be confused or worry about cost issues. This achievement scholarship program is aimed at children of SDN I Glp Minyeuk Sigli in particular so that this program will manage a lot of children's data, in order to be able to manage large children's data quickly and accurately, an information system for receiving achievement scholarships is needed to help in performance so will be fast in processing, processing, and making reports. The purpose of this study was to determine the information system for the Achievement Scholarship Recipients of SDN I Glp Minyeuk Sigli, and to design a desktop-based Information System for the Achievement Scholarship Recipients of SDN I Glp Minyeuk Sigli. Based on the results of observations and the author can draw a conclusion which includes the following, namely; use of the information system for the data collection of outstanding scholarships at SDN 1 Glp. Miyeuk Sigli is expected to be able to help make Achievement Scholarship Information data that is accurate and effective, and the existence of an information system, it makes it easy for SDN 1 Glp. Miyeuk Sigli for speeding up general information and reducing errors.